2004
DOI: 10.1002/ps.892
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ricinus communis (Euphorbiaceae) and ricinine against the leaf‐cutting ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) and the symbiotic fungus Leucoagaricus gongylophorus

Abstract: The focus of this study was the identification of compounds from plant extracts for use in crop protection. This paper reports on the toxic activity of fractions of leaf extracts of Ricinus communis L (Euphorbiaceae) and isolated active compounds in the leaf-cutting ant Atta sexdens rubropilosa Forel and its symbiotic fungus Leucoagaricus gongylophorus (Singer) Möller. The main compounds responsible for activity against the fungus and ant in leaf extracts of R communis were found to be fatty acids for the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 19 publications
3
50
0
1
Order By: Relevance
“…This association is essential for the fungus to draw the nutrients from the plants that the ants carry into their nests [74]. Natural products can be toxic to the symbiotic fungus Leucoagaricus gongylophorus, as observed for those of R. communis (Euphorbiaceae), Helietta puberula (Rutaceae), Simarouba versicolor (Simaroubaceae) and Canavalia ensiformis (Fabaceae) [76][77][78][79]. Baits with plant extracts were effective in the field as a control measure, stopping ant activity between three and 12 days of application [35].…”
Section: Cultural Controlmentioning
confidence: 99%
“…This association is essential for the fungus to draw the nutrients from the plants that the ants carry into their nests [74]. Natural products can be toxic to the symbiotic fungus Leucoagaricus gongylophorus, as observed for those of R. communis (Euphorbiaceae), Helietta puberula (Rutaceae), Simarouba versicolor (Simaroubaceae) and Canavalia ensiformis (Fabaceae) [76][77][78][79]. Baits with plant extracts were effective in the field as a control measure, stopping ant activity between three and 12 days of application [35].…”
Section: Cultural Controlmentioning
confidence: 99%
“…In ingestion tests, the toxicity of plants studied to leaf cutting-ants are not found in literature, but other plants such as Ricinus communis L. (Bigi et al, 2004), Sesamum indicum L. (Morini et al, 2005), Cedrela fissilis Vell , Helietta puberalla RE Fr. (Almeida et al, 2007), Simarouba versicolor St. Hil.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activities of this plant were described (Negi et al, 2011;Medhi et al, 2013), but insecticidal activity was observed only for its fruit essential oil (Prieto et al, 2011). Alkaloids are the main active pharmacological constituents of this plant (Jullian et al, 2006), with promising molecules for the management of leaf cutting-ants (Bigi et al, 2004;Almeida et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggested that toxicity of plants to both leaf-cutting ants and its symbiotic fungus can not be caused by necessarily the same active compounds (Bigi et al 2004, Morini et al 2005. However, H. puberula presented three purified compounds (anthranilic acid, kokusaginine and dictamnine) that were simultaneously toxic to leaf-cutting ants and the Toxicity of Helietta puberula to the leaf-cutting and the symbiotic fungus Almeida et al…”
Section: Resultsmentioning
confidence: 99%
“…and Vismia baccifera (L.) showed toxic effects to Atta cephalotes L. (Hymenoptera: Formicidae) and to its symbiotic fungus. Like these terpenoids isolated from plants, other vegetal species also presented deleterious effects to leaf-cutting ants as well as to symbiotic fungus, for instance Sesamum indicum L. (Bueno et al 1995, Ribeiro et al 1998, Ricinus communis L. (Acácio- Bigi et al 1998, Bigi et al 2004, Ipomoea batatas (L.) (Hebling et al 2000), Canavalia ensiformis (L.) DC (Monteiro et al 1998, Takahashi-Del-Bianco 2002 and more recently for Cedrela fissilis Vell. .…”
mentioning
confidence: 99%